On measurement of the K X-ray absorption jump factors and jump ratios of Gd, Dy, Ho and Er by attenuation of a Compton peak - Mainardi, Raul Torino (2010)
The article entitled "Measurement of the K X-ray absorption jump factors and jump ratios of Gd, Dy, Ho and Er by attenuation of a Compton peak" by Budak G, and Polat R, published in the Journal of Quantitative Spectroscopy and Radiative Transfer 2004;88:525-532, carries out an inadequate treatment of their measured data that renders their results unsuitable for practical use. The analysis and evaluation below describes precisely the mistakes that invalidate the conclusions of this article.